Navigating the Uncommon: PCI to an Anomalous Right Coronary Artery With a Malignant Course Following Failed Arterial Grafts - Ayman Helal; Mohsin Farooq; Mohamed Alama; Ibrahim Antoun (Case Reports in Cardiology)
A 67-year-old male presented with non-ST elevation myocardial infarction (NSTEMI) with underlying anomalous origin of the right coronary artery (RCA) and a malignant course between the aorta and pulmonary artery. Previous CABG with LIMA and RIMA grafts had failed, leaving the patient with severe in-stent restenosis (ISR) in the LAD and degenerated, blocked grafts. The patient underwent percutaneous coronary intervention (PCI) to the anomalous RCA, which posed challenges in engagement due to its anomalous course. This case report discusses the complexities of managing such anatomies, emphasizing the role of CT coronary angiography, the difficulty of engaging anomalous arteries, and the techniques used to achieve successful PCI.